An Elementary Theory of Global Supply Chains - Costinot, A.; Vogel, J.; Wang, S. (Review of Economic Studies, 2013)
This article develops an elementary theory of global supply chains. We consider a world economy with an arbitrary number of countries, one factor of production, a continuum of intermediate goods and one final good. Production of the final good is sequential and subject to mistakes. In the unique free trade equilibrium, countries with lower probabilities of making mistakes at all stages specialize in later stages of production. Using this simple theoretical framework, we offer a first look at how vertical specialization shapes the interdependence of nations. Copyright , Oxford University Press.